2012
DOI: 10.1097/jtn.0b013e31827757a7
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Outcome of Retained Foreign Bodies in Pediatric Gunshot Wounds

Abstract: The purpose of this retrospective review was to determine the long-term consequences of retained bullet foreign bodies in children after gunshot injury. All children managed for gunshot wounds at an urban, level I pediatric trauma center were evaluated, identifying those discharged with retained bullet foreign bodies. Overall, 244 children were treated for gunshot wounds, 107 (44%) had retained foreign bodies, 24 (22%) experienced long-term complications related to retained foreign bodies, and 14 (13%) require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…Many patients discharged from the Emergency Department in the later years of the study did not return for foreign body removal or may have followed up at another institution leading to a false trend. A study of children with retained bullets found that 22% had a complication while 13% required removal, regardless of the body area injured [21]. This study also found 13% of patients undergoing delayed operation, many for retained bullets.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Many patients discharged from the Emergency Department in the later years of the study did not return for foreign body removal or may have followed up at another institution leading to a false trend. A study of children with retained bullets found that 22% had a complication while 13% required removal, regardless of the body area injured [21]. This study also found 13% of patients undergoing delayed operation, many for retained bullets.…”
Section: Discussionmentioning
confidence: 85%
“…Non-operative management of blunt injuries is widely accepted and in the past twenty years non-operative management of penetrating injuries has been discussed in both adult and pediatric populations [19][20][21][22]. There is a high rate of solid organ injury in blunt trauma to the abdomen while firearm and other penetrating injuries often injure hollow organs, requiring operative management [20].…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 48 were Level V evidence, reducing the count to seven studies; hand searching the bibliographies of these yielded one additional study. The final number of studies included in this review therefore was eight, including seven Level IV studies (case series) [1,2,11,15,19,22,28] and one Level III study (retrospective study with a control group) [30] (Table 1).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Indications for late bullet fragment removal were evaluated in a Level IV study performed by Mazotas et al [15]. In this study, which evaluated pediatric patients with retained bullet fragments, 34% of patients had fragmentrelated complications.…”
Section: Selected Indications For Bullet Removalmentioning
confidence: 99%
“…4 Keller and coworkers described 244 children who sustained a fire arm wound during a 3 year study period at our pediatric level-one trauma center. 6 With these limited reports for traumatic wound volume, the scope of caring for a pediatric traumatic wound remains unclear. The literature is even less regarding the cost and morbidity associated with caring for traumatic wounds in children.…”
Section: Introductionmentioning
confidence: 99%